Screening of Antimicrobial and Antioxidant Properties of Ethylenediamine Mono-dithiocarbamate to Overcome the Resistance of Microbes Against Existing Drugs (Journal of Science and Technology Research, 2023)
Excellency of the medical treatment depends on the potentiality of drugs. The increase of the resistance of microbes against drugs is influencing this aspect. Dithiocarbamate has an application in medicine and biology. Therefore, we have synthesized ethylenediamine mono-dithiocarbamate ligand and explored its antimicrobial and antioxidant property. The ligand exhibited moderate antibacterial activity against 13 (thirteen) selected bacteria in disk diffusion method. It showed notable antifungal activity compared to the standard. Therefore, this ligand may be considered as a potential antifungal agent in antifungal drug design. The antioxidant behavior using DPPH assay revealed that this ligand has significant capability in scavenging radicals as compared to standard.J. of Sci. and Tech. Res. 4(1): 183-190, 2022